Improvement of the structural and chemical properties of a commercial activated carbon for its application in electrochemical capacitors - Lota, G.; Centeno, Teresa A.; Frackowiak, E.; Stoeckli, Fritz (My University, 2008)
The present paper shows that the performance of an inexpensive activated carbon used in electrochemical capacitors can be significantly enhanced by a simple treatment with KOH at 850 °C. The changes in the specific surface area, as well as in the surface chemistry, lead to high capacitance values, which provide a noticeable energy density.
The KOH-treatment of a commercial activated carbon leads to highly pure carbons with effective surface areas in the range of 1300–1500 m2 g−1 and gravimetric capacitances as high as three times that of the raw carbon.
For re-activated carbons, one obtains at low current density (50 mA g−1) values of 200 F g−1 in aqueous electrolytes (1M H2SO4 and 6M KOH) and around 150 F g−1 in 1M (C2H5)4NBF4 in acetonitrile. Furthermore, the resulting carbons present an enhanced and stable performance for high charge/discharge load in organic and aqueous media.
This work confirms the possibilities offered by immersion calorimetry on its own for the prediction of the specific capacitance of carbons in (C2H5)4NBF4/acetonitrile. On the other hand, it also shows the limitations of this technique to assess, with a good accuracy, the suitability of a carbon to be used as capacitor electrodes operating in aqueous electrolytes (H2SO4 and KOH).
Keywords: carbon; porosity; pore size distribution; immersion calorimetry; electrochemical capacitor